“Not too Little to go to Hell”: Literary Representations of Childhood in Seventeenth Century England (American & British Studies Annual, 2009)
The paper aims at analyzing the representations of childhood as they were proposed in children’s books written by Puritan authors and preachers, and published in the second half of the XVIIth century. This literature can be considered as a mirror reflecting the different opinions about children English society worked out in this period. So the biographies of “little visible saints” portrayed in books well widespread amongst Puritans reveal us some interesting characteristics, such as the precocity these children showed in reading the Bible, in listening to the sermons, or the constant praying and meditating about religious matters. The different parts of their lives (birth, infancy, sickness and precocious death) are well narrated and investigated in order to detect the so called “marks of election”, an important sign in Calvinist doctrine giving way to salvation in the afterlife. At the same time, their lives are testimonies of extraordinary virtues such as humility, obedience to parents and preachers, perseverance in attending the congregation, respect for the Holy Sabbath, and endurance of pain before death.
Keywords: childhood; children’s books; Puritan; James Janeway; A Token for Children; A Little Book for Children and Youth; Robert Russell; the Bible